Association between genetic polymorphism, severity, and treatment response among COVID-19 infected Egyptian patients - Alaa, Abdelrahman; Sarhan, Neven; Lotfy El-Ansary, Mohamed Gamal; Bazan, Naglaa Samir; Farouk, Khaled; Ismail, Raed Shahat; Schalaan, Mona Farag; Abd-Allah, Adel R. A. (Frontiers in Pharmacology, 2023)
Background: The world has been suffering from the Coronavirus Disease-2019 (COVID-19) pandemic since the end of 2019. The COVID-19-infected patients differ in the severity of the infection and the treatment response. Several studies have been conducted to explore the factors that affect the severity of COVID-19 infection. One of these factors is the polymorphism of the angiotensin converting enzyme 2 (ACE-2) and the type 2 transmembrane serine protease (TMPRSS2) genes since these two proteins have a role in the entry of the virus into the cell. Also, the ACE-1 regulates the ACE-2 expression, so it is speculated to influence the COVID-19 severity. Objective: This study investigates the relationship between the ACE-1, ACE-2, and TMPRSS2 genes single nucleotide polymorphism (SNPs) and the COVID-19 disease severity, treatment response, need for hospitalization, and ICU admission in Egyptian patients. Patients and Methods: The current study is an observational prospective, cohort study, in which 109 total COVID-19 patients and 20 healthy volunteers were enrolled. Of those 109 patients, 51 patients were infected with the non-severe disease and were treated in an outpatient setting, and 58 suffered from severe disease and required hospitalization and were admitted to the ICU. All 109 COVID-19 patients received the treatment according to the Egyptian treatment protocol. Results: Genotypes and allele frequencies among severe and non-severe patients were determined for ACE-1 rs4343, TMPRSS2 rs12329760, and ACE-2 rs908004. The GG genotype and the wild allele of the ACE-2 rs908004 and the mutant allele of the ACE-1 rs4343 were significantly more predominant in severe patients. In contrast, no significant association existed between the TMPRSS2 rs12329760 genotypes or alleles and the disease severity. Conclusion: The results of this study show that the ACE-1 and ACE-2 SNPs can be used as severity predictors for COVID-19 infection since also they have an effect on length of hospitalization.